Class IIa HDACs regulate learning and memory through dynamic experience-dependent repression of transcription - Yongchuan Zhu; Min Huang; Eric Bushong; Sebastien Phan; Marco Uytiepo; Elizabeth Beutter; Daniel Boemer; Kristin Tsui; Mark Ellisman; Anton Maximov (Nature Communications, 2019)
The molecular mechanisms of memory storage remain poorly understood. In this study, authors describe a new mechanism that regulates the cellular patterns of early response gene signaling during learning via the recruitment of two functionally redundant nuclear repressors, class IIa histone deacetylases (HDACs) 4 and 5